Ergativity, Optionality and Markedness in Nepali - Lindemann , Luke (Nepalese Linguistics, 2025)
Nepali presents with a mixed system of split-ergative case-marking where ergativity is obligatory in some domains and optional in others. Where optional, the ergative has an “effector” interpretation that distinguishes it from other optional ergative-marking languages. The mechanisms of optionality and grammaticalized opposition are discussed in the context of Markedness Theory, and Nepali OEM is compared with optional plurality and gender marking in Nepali and English.